I am large, I contain multitude s lyric cohesion and conflict in Second Isaiah - Heffelfinger, Katie M. (Biblical Interpretation Series, 2011)
This book joins the notion that Second Isaiah is a poetic text with the task of interpreting it as a unified whole. In so doing, it makes methodological suggestions for applying a lyric poetic approach to biblical texts. The practical application of this approach shows Second Isaiah to be characterized by tension, conflict, and juxtaposition. The lyric model shows these conflicts, such as the presence of searing indictments in the 'book of comfort,' to be integral elements of the mode by which Second Isaiah addresses its audience. This book highlights the tonalities of the divine voice as central to Second Isaiah's particularly poetic mode of cohesion and essential to the conflicted comfort Second Isaiah offers its reader.